Existence and asymptotic properties of aerotaxis model with the Fokker–Planck type diffusion. (June 2023) - Lee, Jihoon; Yoon, Changwook
Abstract: In this paper, we consider Fokker–Planck type diffusion aerotaxis equations which resemble the usual aerotaxis equations. In view of well-posedness, its own special diffusion structure enables us to take advantage. In two dimensions, we show the existence of global classical solutions under some appropriate conditions. In addition, the stabilization property of the solution is studied, as time approaches infinity. In three dimensions, we prove the existence of global weak solutions.